The elements of style - Strunk, William, 1869-1946; White, E. B. (Elwyn Brooks), 1899-1985 (Penguin Press, 2007)
An enhanced edition of the classic writing manual features humorous art by a popular children's book illustrator and New Yorker cover artist, in a volume that provides visual and whimsical embellishments to the original instructive text--Publisher.